Role of Contrast-Enhanced Ultrasound in the Evaluation of Patients With Suspected Renal Arterial Stenosis - Wang, Yang; Li, Yan; Wang, Siyu; Ma, Na; Ren, Junhong (Frontiers in Cardiovascular Medicine, 2022)
Objectives To explore the role of Contrast-enhanced ultrasound(CEUS) in the evaluation of patients with suspected renal artery stenosis and analyze the causes of the misdiagnosis and missed diagnosis. Methods The data of 40 patients (80 renal arteries) diagnosed with RAS by CEUS in Beijing Hospital from September 2018 to October 2020 were compared with their digital subtraction angiography (DSA) results to analyze the causes underlying missed diagnosis and misdiagnosis of RAS by CEUS. Results 1.Compared with the gold standard DSA results, the AUC of the ROC curve of CEUS in detecting normal renal artery and renal artery stenosis was 0.961, the sensitivity was 96.4%, the specificity was 95.8%, and the Kappa value of the consistency analysis was 0.912 (P＜0.01); 2.Compared with the gold standard DSA results, the ROC curve of CEUS in distinguishing renal artery stenosis ≥ 70% from <70% stenosis has an AUC of 0.916, a sensitivity of 90.9%, a specificity of 92.3%, and the Kappa value of the consistency analysis is 0.77 (P＜0.01); 3.CEUS missed two cases ( one for mild stenosis and one for moderate stenosis), and the detection rate of renal artery stenosis was 97.5% (78/80);A total of 65 renal arteries diagnosed by CEUS were consistent with DSA，and the diagnostic accuracy of CEUS for the degree of stenosis was 81.25% (65/80);Among the 13 misdiagnosed renal arteries, 4 of them can be corrected to the same degree as DSA by the reference to hemodynamic index, and the diagnosis rate of the degree of renal artery stenosis by ultrasonography (combined with CEUS and hemodynamic indicators) can be improved to 86.25%. Conclusions 1.CEUS can clearly show the renal arteries, and is consistent with DSA in distinguishing normal renal artery stenosis from renal artery stenosis, as well as renal artery stenosis ≥70% and <70% stenosis; 2. CEUS showed good performance in detecting normal renal artery and renal artery stenosis, and the missed diagnosis is concentrated on mild and moderate stenosis; 3. CEUS combined with hemodynamic indicators (Doppler ultrasound) can improve the accurate diagnosis rate of renal artery stenosis by ultrasonography; 4...